2019
DOI: 10.1029/2018jc014307
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Vertical Turbulence Mixing Schemes in a Tidally Energetic Environment: 1. 3‐D Shelf‐Sea Model Assessment

Abstract: Mixing in the ocean and shelf seas is critical for the vertical distribution of dynamically active properties, such as density and biogeochemical tracers. Eight different decadal simulations are used to assess the skill of vertical turbulent mixing schemes (TMS) in a 3‐D regional model of tidally active shelf seas. The TMS differ in the type of stability functions used and in the Ozmidov/Deardorff/Galperin limiter of the turbulence length scales. We review the dependence of the critical Richardson and Prandtl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…There are of course differences between model and observed stratification, particularly severe at site D340BH, which is close to the poorly resolved topography of Barra Head. An investigation into the sensitivities of AMM60's ability to reproduce observed stratification is presented elsewhere (Luneva et al., 2019), and is not the focus here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are of course differences between model and observed stratification, particularly severe at site D340BH, which is close to the poorly resolved topography of Barra Head. An investigation into the sensitivities of AMM60's ability to reproduce observed stratification is presented elsewhere (Luneva et al., 2019), and is not the focus here.…”
Section: Discussionmentioning
confidence: 99%
“…Partly in order to resolve this issue, and also to improve model stability, an ad hoc and high level of background diffusion is often applied throughout model domains (Jochum, 2009), justified on the dual grounds of tuning to observations and of numerical stability. This approach can lead to an improvement in reproducing observed levels of mixing in some areas, but often fails to do so within stratified regions (Luneva et al., 2019). Uniformly applied diffusive mixing also fails, by definition, to represent the significant temporal and spatial variability known to exist within ocean turbulence (Moum & Rippeth, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the North Sea, biases in both surface and bottom temperatures ( Figures 1A,B) suggest that stratification errors are linked either to errors in surface forcing or to vertical processes. Experiments with vertical mixing schemes (Luneva et al, 2019) and light attenuation schemes ( Figures 1C,D) suggest that changing these would reduce biases in bottom temperatures. However, there are no flux moorings in the North Sea to evaluate the surface forcing and very few (and infrequent) subsurface observations ( Figure 1E) to evaluate the full depth seasonal cycle.…”
Section: Using Observations To Guide Coastal Model Development and Asmentioning
confidence: 99%
“…The deficit in the predicted mid-water ε points to either an incorrect parameterisation of the small scale physics away from the boundaries or to the absence of key physical processes in the model. A recent study (Luneva et al, 2019) evaluated a range of alternative one dimensional turbulence closure schemes for the Northwest European shelf seas, packaged within the Generic Length Scale two-equation formulation (Umlauf and Burchard, 2005). Evaluating the schemes against profile data (28000 profile in total) confirmed that there was no outright winner, with all schemes under representing the thermocline properties and suggested that physical processes are still missing.…”
Section: Shelf Sea Mixing Processesmentioning
confidence: 99%